Evaluation of Magnesium Die‐Casting Alloys for Elevated Temperature Applications: Castability1 . Issue 6 (24th November 2015) - Easton, Mark A.; Zhu, Suming; Abbott, Trevor B.; Dargusch, Matthew; Murray, Morris; Savage, Gary; Hort, Norbert; Gibson, Mark A.
Abstract : This paper presents a thorough evaluation of the castability of the most common Mg die‐casting alloys developed for elevated temperature applications. The alloys evaluated include AS31, AJ52, MRI153A, MRI153M, MRI230D, AXJ530, AE44, and AM‐HP2plus. Among the various alloys evaluated, AE44, MRI153A, and AS31 are found to have better castability than the other alloys. AM‐HP2plus also has acceptable castability, but it shows signs of hot tearing in some samples. The alloys containing significant levels of Ca, such as MRI153M, MRI230D, and AXJ530, tend to oxidize rapidly, leading to poor melt handling. The comparison of the castability of the selected alloys sheds some light on alloying elements that are of greatest importance in developing a castable alloy. Abstract : The castability of eight "creep resistant" magnesium alloys, together with other five conventional Mg alloys, is assessed in a castability die considering cracking, filling, and spangling. Among all "creep resistant" alloys, AE44, AS31, MRI153A, and HP2plus are found to have very good castability, although they are still inferior to conventional Mg alloys, AZ91 and ZA124 (see figure).